Teenagers Perception of Antisocial Behavior: A Study on First-Year Students at STIKes Cirebon - Nurdianti, Diana; Hikhmat, Rokhmatul; Kurniasih, Uun; Lestari, Sri; Wahyuni, Nuniek Tri; Sumarni, Sumarni (CV. Strata Persada Academia, 2025)
Antisocial behavior is a deviation that violates social norms and can harm individuals and the environment. This study aims to explore the perceptions of first-year students of STIKes Cirebon towards antisocial behavior. A qualitative descriptive approach was used, with data collection through in-depth interviews with five first-year students of the D3 Nursing program aged 18-20 years. Data analysis was conducted using the Miles and Huberman interactive model. The results showed that students had negative perceptions of antisocial behavior, which was considered a violation of norms and a threat to security. Forms of this behavior include intimidation, physical violence, social isolation, and substance abuse, with the leading causes including internal factors such as mental health and external factors such as environmental influences and lack of family supervision. This study emphasizes the importance of family support, social skills, and a positive environment to prevent antisocial behavior. Educational institutions are expected to develop programs to improve student empathy and social skills and build cooperation with families and communities. Parents' education about the importance of supervision also needs to be strengthened. Further research is expected to develop a culture-based and local approach to preventing antisocial behavior.